Gambaran Histologi Pankreas Tikus Wistar yang Diberi Ekstrak Daun Sirsak (Annona muricata L.) Setelah Diinduksi Aloksan - Imanuela P. M. Ticoalu; Sonny J. R. Kalangi; Elvin C. Angmalisang (Jurnal Biomedik:JBM, 2024)
Abstract: Flavonoids, tannins and alkaloids in soursop leaf extract have antioxidant properties which can repair damage to pancreatic beta cells caused by reactive oxygen species. This research was an experimental laboratory study using Wistar rats as research samples. A total of 20 Wistar rats were injected with alloxan with a dose of 170mg/KgBW to achieve hyperglycemia. All sample were divided into four groups, with five rats in each group. Group A (negative control group) was given regular food for 14 days. Group B (positive control group) was given glibenclamide at a dose of 0.09 mg/200 gBW of mice for 14 days. Group C was the group given soursop leaf extract at a dose of 800 mg/KgBW for 14 days, and group C was the group given soursop leaf extract at a dose of 1000 mg/KgBW for 14 days. In the histological description of Wistar rats pancreas in Group C, two out of four islets of Langerhans were found to undergo atrophy, while the exocrine glands appeared normal. In the histological description of Wistar rats pancreas in Group D, one out of six islets of Langerhans was observed to undergo necrosis and amyloid degeneration. Additionally, necrosis and swelling were identified in some epithelial cells of the exocrine glands.  The histological description of Wistar rats pancreas in group D was better compared to the histological description of Wistar rats in other groups. The ratio of the atrophied islets of Langerhans to the total number of islets in this group was smaller compared to the other treatment groups (one out of six). Therefore, it can be concluded that the administration of soursop leaf extract at a dose of 1000 mg/kgBW is more effective in repairing damage caused by the toxic effects of alloxan on the pancreas. Keywords: histology; pancreas; soursop leaves; alloxan   Abtrak: Kandungan flavonoid, tannin, dan alkaloid dalam ekstrak daun sirsak memiliki sifat antioksidan yang dapat memperbaiki kerusakan sel beta pankreas akibat spesies oksigen reaktif. Penelitian ini adalah penelitian eksperimental laboratorium dengan menggunakan tikus wistar sebagai sampel penelitian. Sebanyak 20 ekor tikus Wistar diinduksi menggunakan aloksan dengan dosis 170 mg/KgBB untuk membuat kondisi hiperglikemi kemudian dibagi ke dalam empat kelompok, dengan lima ekor tikus di setiap kelompok. Kelompok A (kontrol negatif) diberi pakan biasa selama 14 hari. Kelompok B (kontrol positif) yang diberi glibenklamid dengan dosis 0,09 mg/200 gBB tikus selama 14 hari. Kelompok C adalah kelompok yang diberikan ekstrak daun sirsak dengan dosis 800 mg/KgBB selama 14 hari, dan kelompok D merupakan kelompok yang diberikan ekstrak daun sirsak dengan dosis 1000 mg/KgBB selama 14 hari. Pada gambaran histologis pankreas tikus wistar kelompok C ditemukan dua dari empat pulau Langerhans mengalami atrofi sementara kelenjar eksokrin normal. Pada gambaran histologis pankreas tikus wistar kelompok D ditemukan satu dari enam pulau Langerhans mengalami nekrosis dan degenerasi amyloid. Ditemukan juga nekrosis dan pembengkakan pada sebagian sel epitel kelenjar eksokrin. Gambaran histologis pankreas tikus wistar kelompok D yang diberi ekstrak daun sirsak dengan dosis 1000 mg/KgBB lebih baik dibandingkan dengan gambaran histologi pankreas tikus ketiga kelompok lain. Perbandingan jumlah pulau Langerhans yang mengalami atrofi dibanding total jumlah pulau Langerhans pada kelompok ini lebih kecil jika dibandingkan dengan kelompok perlakuan lain (satu dari enam pulau). Sehingga dapat disimpulkan bahwa pemberian ekstrak daun sirsak dengan dosis 1000 mg/KgBB lebih baik dalam memperbaiki kerusakan yang diakibatkan oleh efek toksik aloksan terhadap pankreas. Kata kunci: histologi; pankreas; daun sirsak; aloksan